Revisiting the hospital-issued gown in hospitalizations from a locus of control and patient-centered care perspectives: a call for design thinking - Gabay, Gillie; Ornoy, Hana (Frontiers in Public Health, 2024)
Introduction: Patient-centered care (PCC) is the preferred health policy calling to respond to individual patient preferences, wishes, and needs. PCC requires patients to become engaged. While extensive research focused on physicians' robe, research on the hospital-issued patient gown in hospitalizations is scant. How does the gown affect the cognitive-emotional experience of hospitalized patients? How is the gown associated with PCC?The sample of this cross-sectional study comprised 965 patients who were hospitalized at least once during the past year in a tertiary hospital. Measures were previously published.The gown was strongly associated with lack of control, increased distress, was negatively associated with patient proactiveness, engagement, and with taking responsibility for self-management of chronic illness. Compared to males, females wearing the gown had stronger negative emotions, and cognitively strong associations with external locus of control, inhibiting engagement.The hospital gown is an unacknowledged barrier to achieving PCC, inhibits patient-engagement, and reflects paradoxes of inadvertently excluding patients' needs from hospital practice. The hospital gown must be modified to protect the patient's voice and enhance engagement. Policymakers are called to apply design-thinking for facilitating 2 patient participation in decision-making to accord hospital clothing to PCC and improve healthcare delivery.